The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1346/ccmn.1989.0370108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cobalt on the Formation of Crystalline Iron Oxides from Ferrihydrite in Alkaline Media

Abstract: Abstract--At pH 12 Co-ferrihydrite transformed to either Co-goethite or Co-magnetite, the latter compound appearing at Co additions of > 18 mole %. Although Co was readily taken up by the magnetite structure, chemical analysis showed that no more than 7 mole % substitution of Co in goethite was achieved. Hematite formation was not strongly promoted by the presence of Co; with 9 mole % Co in the system, the amount of hematite relative to goethite in the product increased slightly. Co-substituted goethites grew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…A major requirement for isomorphous substitution is a reasonable match between the radii and charges of Fe 3+ (radius 0.64 nm) and the substituent ion (Goldschmidt, 1937). Both Mn 2+ and Co 2+ were oxidized before incorporation into the goethite structure (Stiers & Schwertmann, 1985;Cornell & Giovanoli, 1989). The difference between the radii of these ions and that of Fe 3+ is <20% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A major requirement for isomorphous substitution is a reasonable match between the radii and charges of Fe 3+ (radius 0.64 nm) and the substituent ion (Goldschmidt, 1937). Both Mn 2+ and Co 2+ were oxidized before incorporation into the goethite structure (Stiers & Schwertmann, 1985;Cornell & Giovanoli, 1989). The difference between the radii of these ions and that of Fe 3+ is <20% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In roasting wastes, Co and Ni are mainly present in the Res fraction (>79%), suggesting that most of sulfide-associated Co and Ni were incorporated into silicates or crystalline Fe-oxides during the roasting. Previous studies also suggested that Co and Ni could be easily incorporated into iron oxides via the formation of strong bonds during thermal treatments [15,42,43]. Moreover, thermodynamic analyses predict that CoFe 2 O 4 , NiO·Fe 2 O 3 , and Fe 2 NiO 4 will be major products of the reactions of Co or Ni with iron oxides [35,40].…”
Section: Cobalt and Nickelmentioning
confidence: 94%
“…Initial values of (Co)/(Co + Fe) × 100 mole ratios (x Co ) were 0, 3, 5, 7, and 10 mol% (samples were named G 0 , G 3, G 5, G 7 , and G 10, respectively). After the aging period, the samples were centrifuged, dried at 40 °C, and the amorphous materials were extracted with 0.4 mol/dm 3 HCl at room temperature (Cornell and Giovanoli 1989). The crystalline solids were washed with doubly distilled water until the conductivity of the filtrated solution was similar to that of doubly distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Different aspects of Co-substituted goethite obtained in alkaline media have been studied by other authors (Cornell and Giovanoli 1989;Gerth 1990;Cornell 1991;Gasser et al 1996;Iwasaki and Yamamura 2002). Recent studies of Co-goethites obtained from aerial oxidation of both Fe 2+ and Co 2+ solutions were carried out by Pozas et al (2002Pozas et al ( , 2004.…”
Section: Introductionmentioning
confidence: 99%